Recording with microchannel electrodes in a noisy environment - Fitzgerald, J; Fawcett, J; Lacour, S (2008)
Microchannels containing electrodes have a number of favourable properties that make them potentially suitable as the basis of a peripheral nerve interface design. In this study we have evaluated microchannel recording in vitro in the presence of a realistic simulation of electrical interference from musculature adjacent to an implanted interface. Tripolar recording and high-pass filtration both help improve signal discrimination. At high noise levels designed to replicate the effects of intense muscular activity, a combination of both these techniques is required, and only signals in larger axons can be recovered. © 2008 IEEE.